Child abuse and stress disorders [ - Olive, M. Foster; Collins, Christine E. [ (Christine Elaine)]; Levitt, Patt (Psychological disorders, 2007)
Explores the correlations between child abuse and stress disorders, and discusses the long-term effects of traumatic experiences on both children and adults